Activation of cannabinoid type 2 (CB2) receptors promotes the maintenance of redox homeostasis and protects against oxidative distress in the Neotropical freshwater fish matrinxã Brycon amazonicus (Characiformes: Bryconidae) - Suzana Luisa Alves Fernandes; Yan Costa Gonçalves; Francisco Tadeu Rantin; Ana Lúcia Kalinin; Diana Amaral Monteiro (Neotropical Ichthyology)
Abstract Recent evidence indicates significant interaction of cannabinoid receptors (CB1 and CB2) with redox mechanisms. This study investigated the effects of the cannabinoid agonists WIN 55,212-2 (CB1+CB2) and HU-308 (CB2) on oxidative biomarkers in the liver and heart of the fish Brycon amazonicus. In both the liver and the heart, CB1+CB2 activation led to significant increases in catalase (CAT) and glutathione peroxidase (GPx) activities, accompanied by decreases in glutathione reductase (GR) activity. In contrast, glutathione S-transferase (GST) activity increased in the liver and decreased in the heart following CB1+CB2 activation. In addition, CB1+CB2 agonist had no effect on the GSH/GSSG ratio but increased heart levels of lipoperoxidation (LPO) and hepatic and cardiac protein carbonyl (PC) content. On the other hand, CB2 activation preserved antioxidant enzymatic activities and increased the GSH/GSSG ratio in both tissues. Moreover, the CB2 agonist showed no significant effect on PC levels in either tissue or cardiac LPO levels but decreased hepatic LPO content. In conclusion, activation of CB1+CB2 receptors disrupted the redox balance, leading to oxidative distress and damage, whereas activation of CB2 preserved oxidative eustress. These findings highlight the potential of CB2 receptors to modulate antioxidant defenses and maintain redox homeostasis, critical for improving fish health.